ASSESSMENT OF HOMOCYSTEINE LEVELS IN PATIENTS WITH STROKE IN YOUNG - Saeed Arif (Army Medical College Rawalpindi, 2019)
Objective: To determine the frequency of raised levels of homocysteine and associated socio-demographic factors among the young patients presenting with stroke at the neurology department of a tertiary care hospital of Pakistan.